Perkembangan Anak Ditinjau dari Teori Mature Religion - Putra, Windisyah (Nadwa, 2013)
Physical development is not necessarily equivalent to spiritual development. Normally, a person who has reached maturity level will have spiritual maturity pattern such as thought maturity, personal maturity, and emotional maturity. Yet, the balance between physical maturity and spiritual maturity sometimes does not run in parallel. One may have grown physically but not spiritually. Re-ligious values need to be established in children since early ages. The religious values mean any deeds relating humans and God or among human beings rela-tionship. Physical development is measured based on chronological age, peak of human physical development which is called maturity. On the other hand, spir-itual development is measured based on level of ability and certain ability level achieved by spiritual development which is called maturity.